Clinical recommendations for the inpatient management of lower respiratory tract infections in children and adolescents with severe neurological impairment in Germany - Mauritz, Maximilian David; Both, H. Ulrich von; Dohna-Schwake, Christian; Gille, Christian; Hasan, Carola; Hübner, Johannes; Hufnagel, Markus; Knuf, Markus; Liese, Johannes G.; Renk, Hanna; Rudolph, Henriette; Schulze-Sturm, Ulf; et al. (European journal of pediatrics, 2024)
Children and adolescents with severe neurological impairment (SNI) require specialized care due to their complex medical needs. In particular, these patients are often affected by severe and recurrent lower respiratory tract infections (LRTIs). These infections, including viral and bacterial etiology, pose a significant risk to these patients, often resulting in respiratory insufficiency and long-term impairments. Using expert consensus, we developed clinical recommendations on the management of LRTIs in children and adolescents with SNI. These recommendations emphasize comprehensive multidisciplinary care and antibiotic stewardship. Initial treatment should involve symptomatic care, including hydration, antipyretics, oxygen therapy, and respiratory support. In bacterial LRTIs, antibiotic therapy is initiated based on the severity of the infection, with aminopenicillin plus a beta-lactamase inhibitor recommended for community-acquired LRTIs and piperacillin-tazobactam for patients with chronic lung disease or tracheostomy. Ongoing management includes regular evaluations, adjustments to antibiotic therapy based on pathogen identification, and optimization of supportive care. Implementation of these recommendations aims to improve the diagnosis and treatment of LRTIs in children and adolescents with SNI.What is Known:center dot Children and adolescents with severe neurological impairment are particularly affected by severe and recurrent lower respiratory tract infections (LRTIs).center dot The indication and choice of antibiotic therapy for bacterial LRTI is often difficult because there are no evidence-based treatment recommendations for this heterogeneous but vulnerable patient population; the frequent overuse of broad-spectrum or reserve antibiotics in this patient population increases selection pressure for multidrug-resistant pathogens.What is New:center dot The proposed recommendations provide a crucial framework for focused diagnostics and treatment of LRTIs in children and adolescents with severe neurological impairment.center dot Along with recommendations for comprehensive and multidisciplinary therapy and antibiotic stewardship, ethical and palliative care aspects are taken into account.
Published online: 3 January 2024
Gesehen am 05.11.2024